3D‐Printed Soft Magnetoelectric Microswimmers for Delivery and Differentiation of Neuron‐Like Cells. (1st March 2020) - Dong, Mei; Wang, Xiaopu; Chen, Xiang‐Zhong; Mushtaq, Fajer; Deng, Siyu; Zhu, Caihong; Torlakcik, Harun; Terzopoulou, Anastasia; Qin, Xiao‐Hua; Xiao, Xuanzhong; Puigmartí‐Luis, Josep; Choi, Hongsoo; et al.
Abstract: Neurodegenerative diseases generally result in irreversible neuronal damage and neuronal death. Cell therapy shows promise as a potential treatment for these diseases. However, the therapeutic targeted delivery of these cells and the in situ provision of a suitable microenvironment for their differentiation into functional neuronal networks remain challenging. A highly integrated multifunctional soft helical microswimmer featuring targeted neuronal cell delivery, on‐demand localized wireless neuronal electrostimulation, and post‐delivery enzymatic degradation is introduced. The helical soft body of the microswimmer is fabricated by two‐photon lithography of the photocurable gelatin–methacryloyl (GelMA)‐based hydrogel. The helical body is then impregnated with composite multiferroic nanoparticles displaying magnetoelectric features (MENPs). While the soft GelMA hydrogel chassis supports the cell growth, and is degraded by enzymes secreted by cells, the MENPs allow for the magnetic transportation of the bioactive chassis, and act as magnetically mediated electrostimulators of neuron‐like cells. The unique combination of the materials makes these microswimmers highly integrated devices that fulfill several requirements for their future translation to clinical applications, such as cargo delivery, cell stimulation, and biodegradability. The authors envision that these devices will inspire new avenues for targeted cell therapies for traumatic injuries and diseases in the central nervous system. Abstract : Biodegradable soft magnetoelectric microswimmers are fabricated using a 3D‐printing technique. These microswimmers can perform targeted delivery of neuron‐like cells and induce neuronal differentiation of these cells under different magnetic stimulation modes. This combinatorial technique is a significant step towards highly integrated microrobots, and may open up new avenues for cell therapies.